THE CONCEPTION OF BEATITUDE IN THE PHILOSOPHIES OF FICHTE AND SPINOZA: MORAL AND POLITICAL IMPLICATIONS OF IDEALISM AND DOGMATISM - Scarfia, Lucas Damián (Cadernos Espinosanos, 2023)
In this paper I try to expose the way in which the concept of beatitude (Seligkeit-beatitudo) appears in the thought of Fichte and Spinoza. To this end, I emphasize the importance of considering the metaphysical foundations of their philosophical systems, in order to be able to understand their practical implications - in particular moral and political - regarding the meaning that this concept adopts. Thus, I intend to give an account of the Fichtean metaphysics of the longing (Sehnen) as the basis of his conception of the beatitude in a moral sense. At the same time I aim to compare, in a philosophical-historical sense, this perspective with the Spinozist idea of a beatitude that - leaving morality aside, since politics adopts a primary role in human existence -, from Fichte’s point of view, could only be considered as irrational and dogmatic. The confrontation between the two thinkers intends to favor the understanding of their opposing positions as well as their philosophical systems per se.